Household, its manufacturing method, and application

A fiber-based current collector with adhesive and metal layers addresses the weight and detachment issues of traditional copper and aluminum foils, enhancing battery performance and energy density.

KR103042948B1Active Publication Date: 2026-11-05양저우 나노포어 이너베이티브 머티리얼즈 테크날로지 씨오 엘티디
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020247038453
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-27
Filing Date
2023-05-04
Publication Date
2026-11-05
Estimated Expiration
2043-05-04

AI Technical Summary

Technical Problem

Current lithium-ion battery current collectors, primarily made of pure copper and aluminum foils, are heavy, contributing significantly to battery weight and limiting energy density, and thinner alternatives face issues with strength and detachment on plastic films.

Method used

A current collector comprising a fiber base layer with adhesive and metal layers, where the fiber base layer is composed of composite organic and inorganic fibers, adhesive layers enhance bonding, and metal layers are secured, preventing detachment.

Benefits of technology

The solution achieves weight reduction and increased energy density while preventing metal layer detachment, improving battery performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112024127071592-PCT00001_ABST
    Figure 112024127071592-PCT00001_ABST
Patent Text Reader

Abstract

The present invention relates to the field of battery technology, and specifically, to a current collector, a method of manufacturing the same, and an application thereof. The current collector comprises a fiber base layer, wherein a first adhesive layer and a second adhesive layer are respectively installed on both surfaces of the fiber base layer, and a first metal layer and a second metal layer are respectively installed on the surfaces of the first adhesive layer and the second adhesive layer that are separated from the fiber base layer. The material of the fiber base layer comprises the following compositional parts by weight: 50 to 120 parts of composite fiber, 4.1 to 19 parts of inorganic filler, and an auxiliary agent, wherein the composite fiber includes organic fiber and inorganic fiber. The current collector provided by the present invention can achieve lightweighting of the battery while simultaneously preventing the detachment of the metal layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to the field of battery technology, and specifically, to a current collector, a method of manufacturing the same, and applications. Background Technology

[0002] Currently, the positive and negative current collectors in lithium-ion batteries basically use pure copper foil for the negative electrode and pure aluminum foil for the positive electrode; consequently, the combined mass of these current collectors is heavy, accounting for approximately 15%–20% of the total battery weight. Thinning the positive and negative current collectors can reduce battery weight and increase energy density. However, pure aluminum foil is generally produced using traditional rolling equipment, with a maximum mass-produced thickness of about 8 μm, while pure copper foil is typically an electrolytic copper foil material formed by deposition and extrusion using negative rolls, with a maximum mass-produced thickness of about 6 μm. Due to the limitations of current technological equipment, it is difficult to further reduce the thickness of copper and aluminum foils. Furthermore, once copper and aluminum are transformed into foil materials, their inherent strength decreases, leading to reduced processing performance and making it difficult to achieve even thinner thicknesses.

[0003] Currently, there is research being conducted to reduce battery weight, increase energy density, lower costs, and achieve lightweighting by depositing aluminum or copper onto plastic films (PET films, PVT films, PP films, etc.) using physical or chemical vapor deposition technology to serve as current collectors. However, the plastic films used have high ductility and are easily deformed. In addition, to better compare conductivity with conventional films, it is generally necessary to increase the deposition thickness of the copper or aluminum layer to about 2 μm, but if the thickness of the copper or aluminum layer increases, it can easily detach. The problem to be solved

[0004] Based on this, the present invention provides a current collector capable of realizing lightweighting of a battery while simultaneously preventing the detachment of a metal layer, a method for manufacturing the same, and an application thereof. means of solving the problem

[0005] To realize the above objective of the present invention, the following technical solution is adopted:

[0006] In one aspect of the present invention, a current collector is provided, wherein the current collector comprises a fiber base layer, wherein a first adhesive layer and a second adhesive layer are respectively installed on both surfaces of the fiber base layer, and wherein a first metal layer and a second metal layer are respectively installed on surfaces of the first adhesive layer and the second adhesive layer that are separated from the fiber base layer, and wherein the material composition of the fiber base layer comprises each component in the following weight parts:

[0007] It comprises 50 to 120 parts of composite fibers, 4.1 to 19 parts of inorganic filler, and an auxiliary agent, wherein the composite fibers include organic fibers and inorganic fibers.

[0008] Optionally, in the current collector as described above, the mass ratio of the organic fiber to the inorganic fiber is (70–99.9):(0.1–30).

[0009] Optionally, in the current collector as described above, the mass ratio of the organic fiber to the inorganic fiber is (90–99.9):(0.1–10).

[0010] Optionally, in the current collector as described above, the inorganic filler comprises one or more of calcium carbonate, borax, and nanosilica.

[0011] Optionally, in the current collector as described above, the organic fiber comprises one or more of polyethylene terephthalate fiber, polybutylene terephthalate fiber, polyethylene naphthalate fiber, polypropyl carbamate fiber, urethane fiber, polycaprolactone fiber, nylon 6, nylon 66, polyimide fiber, polyacrylonitrile fiber, polyoxyethylene fiber, polyvinyl alcohol fiber, polyvinyl chloride fiber, polyvinylpyrrolidone fiber, cellulose acetate, ethyl cyanoethyl cellulose, polyaniline fiber, and polybenzimidazole fiber.

[0012] Optionally, in the current collector as described above, the inorganic fiber comprises one or more of graphene fibers, carbon fibers, glass fibers, ceramic fibers, metal oxide nanofibers, and silica nanofibers.

[0013] Optionally, in the current collector as described above, the auxiliary agent comprises one or more of a dispersant, a thickener, an emulsifier, and an adhesive;

[0014] The above dispersant comprises one or more of polyacrylamide, polyvinyl alcohol, sodium citrate, and sodium silicate;

[0015] The above-mentioned thickener comprises one or more of hydroxypropylmethylcellulose sodium, hydroxyethylmethylcellulose sodium, carboxymethylcellulose sodium, methylcellulose sodium, and sodium algilate;

[0016] The above emulsifier comprises one or more of glyceryl monostearate, polyethylene oxide, and sodium dodecyl sulfate;

[0017] The above adhesive comprises sodium carboxymethylcellulose and / or polyvinyl alcohol.

[0018] Optionally, in the current collector as described above, the amount of additive in the fiber base layer is 8.1 to 28 parts by weight, and in the additive, the dispersant is 2.5 to 9 parts by weight, the thickener is 3 to 8 parts by weight, the emulsifier is 0.1 to 2 parts by weight, and the adhesive is 2.5 to 9 parts by weight.

[0019] Optionally, the entire structure as described above further comprises a first antioxidant layer and a second antioxidant layer, wherein the first antioxidant layer is located on a surface of the first metal layer separated from the first adhesive layer, and the second antioxidant layer is located on a surface of the second metal layer separated from the second adhesive layer.

[0020] Optionally, in the current collector as described above, the materials of the first adhesive layer and the second adhesive layer are each independently Ni, Zn, Fe, Gr, SiO 2,Al2O 3, It is Fe2O3 or Si3N4.

[0021] Optionally, in the current collector as described above, the materials of the first metal layer and the second metal layer are Al, Cu, or Zn.

[0022] Optionally, in the current collector as described above, the materials of the first antioxidant layer and the second antioxidant layer are each independently Al, Fe, Ni, Zn, Gr, SiO2, Al2O 3, It is SiC or Si3N4.

[0023] Optionally, in the current collector as described above, the thickness of the fiber base layer is 2 μm to 8 μm.

[0024] Optionally, in the current collector as described above, the thickness of the first adhesive layer and the second adhesive layer are each independently 10 nm to 200 nm.

[0025] Optionally, in the current collector as described above, the thickness of the first metal layer and the second metal layer are each independently 100 nm to 2000 nm.

[0026] Optionally, in the current collector as described above, the thickness of the first antioxidant layer and the second antioxidant layer are each independently 10 nm to 100 nm.

[0027] Optionally, in the current collector as described above, at least one of the first adhesive layer and the second adhesive layer is made of Fe, and the inorganic fiber comprises one or more of graphene fibers and carbon fibers.

[0028] Optionally, in the current collector as described above, the inorganic fiber is selected from metal oxide nanofibers, and the materials of the first adhesive layer and the second adhesive layer are each independently selected from metal or metal oxide.

[0029] Optionally, in the current collector as described above, the inorganic fiber comprises one or more of graphene fibers, carbon fibers, glass fibers, ceramic fibers, and silica nanofibers, and the materials of the first adhesive layer and the second adhesive layer are each independently selected from non-metallic oxides and non-metallic nitrides.

[0030] In one aspect of the present invention, a method for manufacturing a current collector as described above is provided, wherein the method comprises:

[0031] A step of manufacturing the fiber base layer by mixing the composite fiber, the inorganic filler, and the auxiliary agent, and then rolling and molding;

[0032] A step of forming the first adhesive layer and the second adhesive layer on each of the two sides of the fiber base layer; and

[0033] The step of forming the first metal layer and the second metal layer, respectively, on one surface of the first adhesive layer and the second adhesive layer separated from the fiber base layer; is included.

[0034] In another aspect of the present invention, an electrode sheet is further provided comprising a current collector as described above and an electrode active material layer located on the surface of said current collector.

[0035] In another aspect of the present invention, a battery cell comprising an electrode sheet as described above is provided.

[0036] In one aspect of the present invention, a battery pack comprising a plurality of battery cells as described above is further provided.

[0037] In another aspect of the present invention, an electric device comprising a battery cell or a battery pack as described above is further provided. Effects of the invention

[0038] The fiber base layer provided in the present invention has a low elongation and does not deform easily, and there is no need to punch the surface of the fiber base layer. Furthermore, good bonding between the first metal layer and the second metal layer can be realized through the action of the first adhesive layer and the second adhesive layer, thereby preventing the detachment of the first metal layer and the second metal layer and solving the problem of weakened or lost battery performance caused by the detachment of the first metal layer and the second metal layer. In addition, the fiber base layer can achieve weight reduction of the current collector, thereby reducing the overall weight of the battery and increasing energy density. Moreover, the introduction of the fiber base layer is advantageous for the penetration of the current collector and the electrolyte, thereby improving the efficiency of the battery injection process, increasing battery magnification performance, and enhancing the stability of the battery.

[0039] In summary, the current collector provided by the present invention can achieve weight reduction of the battery and improve the energy density of the battery, while simultaneously preventing the detachment of the metal coating layer and reducing the manufacturing costs of the current collector and the battery. Brief explanation of the drawing

[0040] In order to more clearly explain the specific embodiments of the present invention or the technical methods of the prior art, a brief description of the drawings to be used in the description of the specific embodiments or prior art is provided below. The drawings described below represent only some embodiments of the present invention, and it is obvious that a person skilled in the art can obtain other related drawings based on these drawings without requiring creative labor. FIG. 1 is a schematic diagram of the structure of a current collector manufactured in one embodiment of the present invention. Drawing symbol description: 100-Fiber base layer; 200-1st adhesive layer; 300-1st metal layer; 400-1st antioxidant layer; 500-2nd adhesive layer; 600-2nd metal layer; 700-2nd antioxidant layer. Specific details for implementing the invention

[0041] Embodiments of the present invention are provided in detail by reference, and one or more examples are described below. Each example is provided as an interpretation of the present invention, not as a limitation to the present invention. In practice, it is obvious to those skilled in the art that various modifications and changes can be made to the present invention without departing from the scope or spirit of the present invention. For example, a function described or explained as part of one embodiment may be used in other embodiments to create additional embodiments.

[0042] Accordingly, the present invention includes such modifications and changes falling within the scope of the appended claims and equivalents. Other subjects, features, and aspects of the present invention are disclosed in or will become apparent from the detailed description below. Those skilled in the art should understand that this discussion is not intended to limit the broader aspects of the invention but is merely a description of exemplary embodiments.

[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as generally understood by a person skilled in the art of the present invention. The terms used in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the invention. As used herein, the term "and / or" includes any and all combinations of one or more related listed items.

[0044] Conventional current collectors are heavy, which increases the total weight of the battery and lowers energy density. Furthermore, plastic films currently used to reduce the weight of current collectors have high elongation and deform easily, and the deposited metal layer detaches easily, making it difficult to achieve substantial improvement in battery performance. To this end, the present invention provides a current collector to solve the aforementioned problems.

[0045] A current collector according to the present invention comprises a fiber base layer, wherein a first adhesive layer and a second adhesive layer are respectively installed on both surfaces of the fiber base layer, and a first metal layer and a second metal layer are respectively installed on surfaces of the first adhesive layer and the second adhesive layer that are separated from the fiber base layer, and the material of the fiber base layer comprises each of the following compositional parts by weight:

[0046] It comprises 50 to 120 parts of composite fibers, 4.1 to 19 parts of inorganic filler, and an auxiliary agent, wherein the composite fibers include organic fibers and inorganic fibers.

[0047] The fiber base layer has a low elongation and does not deform easily, and there is no need to punch the surface of the fiber base layer. Through the action of the first adhesive layer and the second adhesive layer, good bonding between the first metal layer and the second metal layer can be realized, thereby preventing the detachment of the first metal layer and the second metal layer and solving the problem of weakened or lost battery performance caused by the detachment of the first metal layer and the second metal layer. In addition, the fiber base layer can achieve weight reduction of the current collector, thereby reducing the overall weight of the battery and increasing energy density. Furthermore, the introduction of the fiber base layer is advantageous for the penetration of the current collector and the electrolyte, thereby improving the efficiency of the battery injection process, increasing battery magnification performance, and improving the stability of the battery.

[0048] In summary, the current collector provided by the present invention can achieve weight reduction of the battery and improve the energy density of the battery, while simultaneously preventing the detachment of the metal coating layer and reducing the manufacturing costs of the current collector and the battery.

[0049] In some embodiments, the composite fiber may be any value between 50 and 120 parts, for example, 55 parts, 60 parts, 65 parts, 70 parts, 80 parts, 90 parts, 100 parts, and 110 parts.

[0050] In some embodiments, the mass ratio of organic fibers to inorganic fibers may be any value between (70 to 99.9):(0.1 to 30), and may be 80:20, 82:18, 85:15, 87:13, 90:10, 92:8, 95:5, 98:2.

[0051] In some embodiments, the organic fiber may be any organic fiber conventional in the art and includes, but is not limited to, one or more of polyethylene terephthalate (PET) fiber, polybutylene terephthalate (PBT) fiber, polyethylene naphthalate (PEN) fiber, polypropyl carbamate fiber, urethane (PU) fiber, polycaprolactone (PCL) fiber, nylon 6, nylon 66, polyimide (PI) fiber, polyacrylonitrile (PAN) fiber, polyoxyethylene (PEO) fiber, polyvinyl alcohol (PVA) fiber, polyvinyl chloride (PVC) fiber, polyvinylpyrrolidone (PVP) fiber, cellulose acetate, ethyl cyanoethyl cellulose, polyaniline fiber, and polybenzimidazole fiber. Preferably, the organic fiber is one or more of nylon 6, nylon 66, polyimide fiber, and polyacrylonitrile fiber.

[0052] In some embodiments, the inorganic fiber may be any inorganic fiber conventional in the art and may include, but is not limited to, one or more of graphene fibers, carbon fibers, glass fibers, ceramic fibers, metal oxide nanofibers, and silica nanofibers. Preferably, the inorganic fiber is a metal oxide nanofiber. Here, the metal oxide nanofiber includes one or more of aluminum oxide nanofibers, zinc oxide nanofibers, zirconium oxide nanofibers, magnesium oxide nanofibers, titanium dioxide nanofibers, and tin oxide nanofibers. Here, the graphene fiber is a fibrous material composed of graphene monolayers.

[0053] In some embodiments, the inorganic filler comprises one or more of calcium carbonate, borax, and nanosilica. By adding the inorganic filler, the mechanical performance and heat resistance of the fiber base layer can be improved. Preferably, the inorganic filler is calcium carbonate, borax, and nanosilica.

[0054] In some embodiments, the calcium carbonate in the inorganic filler is 2 to 8 parts by weight, borax is 2 to 10 parts by weight, and nano silica is 0.1 to 1 part by weight.

[0055] In some embodiments, the auxiliary agent may include one or more of a dispersant, a thickener, an emulsifier, and an adhesive. Here, the dispersant may be one or more of polyacrylamide, polyvinyl alcohol, sodium citrate, and sodium silicate; the thickener may be one or more of sodium hydroxypropylmethylcellulose, sodium hydroxyethylmethylcellulose, sodium carboxymethylcellulose, sodium methylcellulose, and sodium algilate; the emulsifier may be one or more of glyceryl monostearate, polyethylene oxide, and sodium dodecyl sulfate; and the adhesive may be sodium carboxymethylcellulose and / or polyvinyl alcohol.

[0056] In some embodiments, the amount of auxiliary agent added to the fiber base layer may be 8.1 to 28 parts by weight, and among the auxiliary agents, the dispersant may be 2.5 to 9 parts by weight, the thickener 3 to 8 parts by weight, the emulsifier 0.1 to 2 parts by weight, and the adhesive 2.5 to 9 parts by weight.

[0057] In some embodiments, the thickness of the fiber base layer may be any value between 2 μm and 8 μm, and may be, for example, 2.5 μm, 4 μm, 5.5 μm, 6 μm, or 7 μm.

[0058] In some embodiments, 4 g / cm² 3 ~4.1g / cm 3 The tensile elongation of the fiber base layer at the compaction density is 0.2% to 0.4%, which is much lower than the elongation of conventional copper foil or aluminum foil (>0.6%), and the current collector manufactured in this way has a lower elongation and does not deform easily.

[0059] In some embodiments, the surface of the fiber base layer may have a pore structure or may not have a pore structure, and if there is a pore structure, the average pore size may be 5 nm to 500 nm and the porosity may be 0.1% to 50%.

[0060] In some embodiments, the thickness of the first adhesive layer and the second adhesive layer may each independently be any value between 10 nm and 200 nm, and may be, for example, 30 nm, 50 nm, 100 nm, 130 nm, 150 nm, or 180 nm.

[0061] In some embodiments, the materials of the first adhesive layer and the second adhesive layer may each be independently selected from metal or non-metal compounds, wherein the metal may be Ni, Zn, Fe, or Gr, and the non-metal compound may be mainly oxides and nitrides, for example, SiO2, Al2O3, Fe2O3, or Si3N4, wherein the non-metal compound is further divided into a compound containing a metal element and a compound not containing a metal element, wherein the compound containing a metal element may mainly include a metal oxide, for example, Al2O3 or Fe2O3, and the compound not containing a metal element may mainly include a non-metal oxide and a non-metal nitride, for example, SiO2 or Si3N4.

[0062] In some embodiments, the inorganic fiber is selected from metal oxide nanofibers, and the materials of the first adhesive layer and the second adhesive layer are each independently selected from metal or non-metal compounds.

[0063] In some embodiments, the inorganic fiber comprises titanium dioxide nanofibers, and the materials of the first adhesive layer and the second adhesive layer are each independently selected from Ni and Fe2O3.

[0064] In some embodiments, the inorganic fiber is selected from one or more of graphene fibers, carbon fibers, glass fibers, ceramic fibers, and silica nanofibers, and the materials of the first adhesive layer and the second adhesive layer may each be independently selected from non-metallic oxides and non-metallic nitrides, for example, SiO2 or Si3N4.

[0065] In some embodiments, the inorganic fiber is selected from one or more of glass fibers, ceramic fibers and silica nanofibers, and the materials of the first adhesive layer and the second adhesive layer are each independently selected from SiO2 or Si3N4.

[0066] In some embodiments, the inorganic fiber is selected from one or more of graphene fibers and carbon fibers, and the materials of the first adhesive layer and the second adhesive layer are each independently selected from Ni, Zn, Fe, and Gr.

[0067] In some embodiments, the inorganic fiber is selected from one or more of graphene fibers and carbon fibers, and at least one of the first adhesive layer and the second adhesive layer is made of Fe.

[0068] In some embodiments, the thickness of the first metal layer and the second metal layer may each independently be any value between 100 nm and 2000 nm, for example, 150 nm, 200 nm, 300 nm, 500 nm, 800 nm, 1200 nm, 1500 nm, and 1800 nm.

[0069] In some embodiments, the materials of the first metal layer and the second metal layer may be Al, Cu, or Zn.

[0070] In some embodiments, the current collector further comprises a first antioxidant layer and a second antioxidant layer, wherein the first antioxidant layer is located on one side separated from the first adhesive layer of the first metal layer, and the second antioxidant layer is located on one side separated from the second adhesive layer of the second metal layer. The introduction of the antioxidant layer can prevent oxidation of the first metal layer and the second metal layer, and further prevent detachment of the first metal layer and the second metal layer.

[0071] In some embodiments, the thickness of the first antioxidant layer and the second antioxidant layer may each independently be any value between 10 nm and 100 nm, and may be, for example, 20 nm, 50 nm, 70 nm, or 90 nm.

[0072] In some embodiments, the materials of the first antioxidant layer and the second antioxidant layer may each be independently selected from metals, metal oxides, and nonmetal compounds, wherein the metal may be Al, Fe, Ni, Zn, or Gr, the metal oxide may be Fe2O3 or Al2O3, and the nonmetal compound may be mainly carbides and nitrides, for example, SiC or Si3N4. Preferably, when the materials of the first metal layer and the second metal layer are Cu, the materials of the first antioxidant layer and the second antioxidant layer may each independently be Al, Fe, Ni, Zn, Fe2O3, Al2O3, or SiC, and when the materials of the first metal layer and the second metal layer are Al, the materials of the first antioxidant layer and the second antioxidant layer may each independently be Ni, Gr, Al2O3, or Si3N4.

[0073] In one aspect of the present invention, a method for manufacturing a current collector as described above is further provided, said manufacturing method is:

[0074] A step of manufacturing a fiber base layer by mixing composite fibers, inorganic fillers, and auxiliary agents, and then rolling and molding;

[0075] A step of forming a first adhesive layer and a second adhesive layer on each side of a fiber base layer; and

[0076] The step of forming a first metal layer and a second metal layer, respectively, on one surface separated from the fiber base layer of the first adhesive layer and the second adhesive layer; is included.

[0077] In some embodiments, the specific step of manufacturing the fiber base layer may be to mix the composite fiber, inorganic filler, and auxiliary agent, lay them in a net, and then form them by hot rolling and drying.

[0078] In some embodiments, the method of forming the first adhesive layer, the second adhesive layer, the first metal layer, and the second metal layer may be any method known in the art, such as vacuum deposition.

[0079] In another aspect of the present invention, an electrode sheet is further provided comprising a current collector as described above and an electrode active material layer located on the surface of the current collector.

[0080] In another aspect of the present invention, a battery cell comprising an electrode sheet as described above is provided.

[0081] In one aspect of the present invention, a battery pack comprising a plurality of battery cells as described above is further provided.

[0082] In another aspect of the present invention, an electric device comprising a battery cell or a battery pack as described above is further provided.

[0083] The present invention will be described in more detail below by combining specific embodiments and comparative examples.

[0084] Example 1

[0085] A schematic diagram of the structure of the current collector manufactured in this embodiment is shown in FIG. 1. As can be seen from FIG. 1, the current collector comprises a fiber base layer (100), wherein a first adhesive layer (200) and a second adhesive layer (500) are respectively installed on both surfaces of the fiber base layer (100), and a first metal layer (300) and a second metal layer (600) are respectively installed on one side of the first adhesive layer (200) and the second adhesive layer (500) separated from the fiber base layer (100), and a first antioxidant layer (400) and a second antioxidant layer (700) are respectively installed on one side of the first metal layer (300) and the second metal layer (600) separated from the first adhesive layer (200) and the second adhesive layer (500). The specific manufacturing steps of the fiber current collector are specifically as follows:

[0086] 1) Manufacturing of fiber base layer (100)

[0087] Nylon 6 and titanium dioxide nanofibers with a mass ratio of 98:2 are mixed, melted, and then extruded to form composite fibers. Then, 50 parts of composite fibers, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica are taken, uniformly mixed, laid out uniformly in a net shape, and hot-rolled and dried to produce a fiber base layer (100) with a thickness of 6 μm.

[0088] 2) Manufacture of the entire house

[0089] A first adhesive layer (200) and a second adhesive layer (500), each having a thickness of 50 nm, are respectively deposited on the upper and lower surfaces of the fiber base layer (100) manufactured in step 1) using vacuum deposition technology, wherein the first adhesive layer (200) and the second adhesive layer (500) are nickel metal layers. Then, a first metal layer (300) and a second metal layer (600), each having a thickness of 1000 nm, are continuously deposited on the first adhesive layer (200) and the second adhesive layer (500), wherein the first metal layer (300) and the second metal layer (600) are aluminum metal layers. Then, a first antioxidant layer (400) and a second antioxidant layer (700) with a thickness of 50 nm are continuously deposited on the first metal layer (300) and the second metal layer (600) (where the first antioxidant layer (400) and the second antioxidant layer (700) are nickel metal layers) to obtain an aluminum current collector. A related performance test is performed on this, and the test results are as shown in Table 1.

[0090] Example 2

[0091] The method of manufacturing the current collector and the structure of the current collector of this embodiment and Example 1 are basically the same, except that: the first metal layer (300) and the second metal layer (600) in step 2) are copper metal layers, and a copper current collector is manufactured. A related performance test was performed on this, and the test results are shown in Table 1.

[0092] Example 3

[0093] The method of manufacturing the current collector and the structure of the current collector of this embodiment and Example 1 are basically the same, and the difference is: the composition of the fiber base layer (100) is different. The specific manufacturing steps of the current collector are specifically as follows:

[0094] 1) Manufacturing of fiber base layer (100)

[0095] Nylon 6 and titanium dioxide nanofibers with a mass ratio of 98:2 are mixed, melted, and then extruded to form composite fibers. Then, 80 parts of composite fibers, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica are taken, uniformly mixed, laid out uniformly in a net shape, and hot-rolled and dried to produce a fiber base layer (100) with a thickness of 6 μm.

[0096] 2) Manufacture of the entire house

[0097] A first adhesive layer (200) and a second adhesive layer (500), each having a thickness of 50 nm, are respectively deposited on the upper and lower surfaces of the fiber base layer (100) manufactured in step 1) using vacuum deposition technology, wherein the first adhesive layer (200) and the second adhesive layer (500) are SiO2 layers. Then, a first metal layer (300) and a second metal layer (600), each having a thickness of 1000 nm, are continuously deposited on the first adhesive layer (200) and the second adhesive layer (500), wherein the first metal layer (300) and the second metal layer (600) are aluminum metal layers. Then, a first antioxidant layer (400) and a second antioxidant layer (700) with a thickness of 50 nm are continuously deposited on the first metal layer (300) and the second metal layer (600) (where the first antioxidant layer (400) and the second antioxidant layer (700) are Al2O3 layers) to obtain an aluminum current collector. A related performance test is performed on this, and the test results are as shown in Table 1.

[0098] Example 4

[0099] The method of manufacturing the current collector and the structure of the current collector in this embodiment and embodiment 3 are basically the same, and the difference is that the first metal layer (300) and the second metal layer (600) in step 2) are copper metal layers, and the first antioxidant layer (400) and the second antioxidant layer (700) are SiC layers, and a copper current collector is manufactured. Accordingly, relevant performance tests were performed, and the test results are shown in Table 1.

[0100] Example 5

[0101] The method of manufacturing the current collector and the structure of the current collector of this embodiment and Example 1 are basically the same, and the difference is: the composition of the fiber base layer (100) is different. The specific manufacturing steps of the current collector are specifically as follows:

[0102] 1) Manufacturing of fiber base layer (100)

[0103] Polyimide fibers and glass fibers with a mass ratio of 98:2 are mixed, melted, and then extruded to form composite fibers. Then, 120 parts of composite fibers, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica are taken, uniformly mixed, laid out uniformly in a net shape, and hot-rolled and dried to produce a fiber base layer (100) with a thickness of 6 μm.

[0104] 2) Manufacture of the entire house

[0105] A first adhesive layer (200) and a second adhesive layer (500), each having a thickness of 40 nm, are respectively deposited on the upper and lower surfaces of the fiber base layer (100) manufactured in step 1) using vacuum deposition technology, wherein the first adhesive layer (200) and the second adhesive layer (500) are nickel metal layers. Then, a first metal layer (300) and a second metal layer (600), each having a thickness of 1000 nm, are continuously deposited on the first adhesive layer (200) and the second adhesive layer (500), wherein the first metal layer (300) and the second metal layer (600) are aluminum metal layers. Then, a first antioxidant layer (400) and a second antioxidant layer (700) with a thickness of 40 nm are continuously deposited on the first metal layer (300) and the second metal layer (600) (where the first antioxidant layer (400) and the second antioxidant layer (700) are nickel metal layers) to obtain an aluminum current collector. A related performance test is performed on this, and the test results are as shown in Table 1.

[0106] Example 6

[0107] The method of manufacturing the current collector and the structure of the current collector in this embodiment and embodiment 5 are basically the same, except that: the first metal layer (300) and the second metal layer (600) in step 2) are copper metal layers, and a copper current collector is manufactured. A related performance test was performed on this, and the test results are shown in Table 1.

[0108] Example 7

[0109] The method of manufacturing the current collector and the structure of the current collector of this embodiment and Example 1 are basically the same, and the difference is: the composition of the fiber base layer (100) is different. The specific manufacturing steps of the current collector are specifically as follows:

[0110] 1) Manufacturing of fiber base layer (100)

[0111] Polyacrylonitrile fibers and silica nanofibers with a mass ratio of 85:15 are mixed, melted, and then extruded to form composite fibers. Then, 50 parts of composite fibers, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica are taken, uniformly mixed, laid out uniformly in a net shape, and hot-rolled and dried to produce a fiber base layer (100) with a thickness of 6 μm.

[0112] 2) Manufacture of the entire house

[0113] A first adhesive layer (200) and a second adhesive layer (500), each having a thickness of 50 nm, are respectively deposited on the upper and lower surfaces of the fiber base layer (100) manufactured in step 1) using vacuum deposition technology, wherein the first adhesive layer (200) and the second adhesive layer (500) are nickel metal layers. Then, a first metal layer (300) and a second metal layer (600), each having a thickness of 1000 nm, are continuously deposited on the first adhesive layer (200) and the second adhesive layer (500), wherein the first metal layer (300) and the second metal layer (600) are aluminum metal layers. Then, a first antioxidant layer (400) and a second antioxidant layer (700) with a thickness of 50 nm are continuously deposited on the first metal layer (300) and the second metal layer (600) (where the first antioxidant layer (400) and the second antioxidant layer (700) are nickel metal layers) to obtain an aluminum current collector. A related performance test is performed on this, and the test results are as shown in Table 1.

[0114] Example 8

[0115] The method of manufacturing the current collector and the structure of the current collector of the present embodiment and Example 7 are basically the same, and the difference is: the materials of the first adhesive layer (200) and the second adhesive layer (500) are different. The specific manufacturing steps of the current collector are specifically as follows:

[0116] 1) Manufacturing of fiber base layer (100)

[0117] Polyacrylonitrile fibers and silica nanofibers with a mass ratio of 85:15 are mixed, melted, and then extruded to form composite fibers. Then, 50 parts of composite fibers, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica are taken, uniformly mixed, laid out uniformly in a net shape, and hot-rolled and dried to produce a fiber base layer (100) with a thickness of 6 μm.

[0118] 2) Manufacture of the entire house

[0119] A first adhesive layer (200) and a second adhesive layer (500), each having a thickness of 50 nm, are respectively deposited on the upper and lower surfaces of the fiber base layer (100) manufactured in step 1) using vacuum deposition technology, wherein the first adhesive layer (200) and the second adhesive layer (500) are SiO2 layers. Then, a first metal layer (300) and a second metal layer (600), each having a thickness of 1000 nm, are continuously deposited on the first adhesive layer (200) and the second adhesive layer (500), wherein the first metal layer (300) and the second metal layer (600) are aluminum metal layers. Then, a first antioxidant layer (400) and a second antioxidant layer (700) with a thickness of 50 nm are continuously deposited on the first metal layer (300) and the second metal layer (600) (where the first antioxidant layer (400) and the second antioxidant layer (700) are nickel metal layers) to obtain an aluminum current collector. A related performance test is performed on this, and the test results are as shown in Table 1.

[0120] Example 9

[0121] The method of manufacturing the current collector and the structure of the current collector of the present embodiment and Example 6 are basically the same, and the difference is: the materials of the first adhesive layer (200) and the second adhesive layer (500) are different. The specific manufacturing steps of the current collector are specifically as follows:

[0122] 1) Manufacturing of fiber base layer (100)

[0123] Polyimide fibers and glass fibers with a mass ratio of 98:2 are mixed, melted, and then extruded to form composite fibers. Then, 120 parts of composite fibers, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica are taken, uniformly mixed, laid out uniformly in a net shape, and hot-rolled and dried to produce a fiber base layer (100) with a thickness of 6 μm.

[0124] 2) Manufacture of the entire house

[0125] A first adhesive layer (200) and a second adhesive layer (500), each having a thickness of 40 nm, are respectively deposited on the upper and lower surfaces of the fiber base layer (100) manufactured in step 1) using vacuum deposition technology, wherein the first adhesive layer (200) and the second adhesive layer (500) are SiO2 layers. Then, a first metal layer (300) and a second metal layer (600), each having a thickness of 1000 nm, are continuously deposited on the first adhesive layer (200) and the second adhesive layer (500), wherein the first metal layer (300) and the second metal layer (600) are copper metal layers. Then, a first antioxidant layer (400) and a second antioxidant layer (700) with a thickness of 40 nm are continuously deposited on the first metal layer (300) and the second metal layer (600) (where the first antioxidant layer (400) and the second antioxidant layer (700) are nickel metal layers) to obtain a copper current collector. A related performance test is performed on this, and the test results are as shown in Table 1.

[0126] Example 10

[0127] The method of manufacturing the current collector and the structure of the current collector of this embodiment and Example 1 are basically the same, and the difference is: the materials of the first adhesive layer (200) and the second adhesive layer (500) are different. The specific manufacturing steps of the current collector are specifically as follows:

[0128] 1) Manufacturing of fiber base layer (100)

[0129] Nylon 6 and titanium dioxide nanofibers with a mass ratio of 98:2 are mixed, melted, and then extruded to form composite fibers. Then, 50 parts of composite fibers, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica are taken, uniformly mixed, laid out uniformly in a net shape, and hot-rolled and dried to produce a fiber base layer (100) with a thickness of 6 μm.

[0130] 2) Manufacture of the entire house

[0131] A first adhesive layer (200) and a second adhesive layer (500), each having a thickness of 50 nm, are respectively deposited on the upper and lower surfaces of the fiber base layer (100) manufactured in step 1) using vacuum deposition technology, wherein the first adhesive layer (200) and the second adhesive layer (500) are Fe2O3 layers. Then, a first metal layer (300) and a second metal layer (600), each having a thickness of 1000 nm, are continuously deposited on the first adhesive layer (200) and the second adhesive layer (500), wherein the first metal layer (300) and the second metal layer (600) are aluminum metal layers. Then, a first antioxidant layer (400) and a second antioxidant layer (700) with a thickness of 50 nm are continuously deposited on the first metal layer (300) and the second metal layer (600) (where the first antioxidant layer (400) and the second antioxidant layer (700) are nickel metal layers) to obtain an aluminum current collector. A related performance test is performed on this, and the test results are as shown in Table 1.

[0132] Example 11

[0133] The method of manufacturing the current collector and the structure of the current collector of this embodiment and Example 1 are basically the same, and the difference is: the materials of the first adhesive layer (200) and the second adhesive layer (500) are different. The specific manufacturing steps of the current collector are specifically as follows:

[0134] 1) Manufacturing of fiber base layer (100)

[0135] Nylon 6 and graphene fibers with a mass ratio of 98:2 are mixed, melted, and then extruded to form composite fibers. Then, 50 parts of composite fibers, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica are taken, uniformly mixed, laid out uniformly in a net shape, and hot-rolled and dried to produce a fiber base layer (100) with a thickness of 6 μm.

[0136] 2) Manufacture of the entire house

[0137] A first adhesive layer (200) and a second adhesive layer (500), each having a thickness of 50 nm, are respectively deposited on the upper and lower surfaces of the fiber base layer (100) manufactured in step 1) using vacuum deposition technology, wherein the first adhesive layer (200) and the second adhesive layer (500) are iron metal layers. Then, a first metal layer (300) and a second metal layer (600), each having a thickness of 1000 nm, are continuously deposited on the first adhesive layer (200) and the second adhesive layer (500), wherein the first metal layer (300) and the second metal layer (600) are aluminum metal layers. Then, a first antioxidant layer (400) and a second antioxidant layer (700) with a thickness of 50 nm are continuously deposited on the first metal layer (300) and the second metal layer (600) (where the first antioxidant layer (400) and the second antioxidant layer (700) are nickel metal layers) to obtain an aluminum current collector. A related performance test is performed on this, and the test results are as shown in Table 1.

[0138] Example 12

[0139] The method of manufacturing the current collector and the structure of the current collector in this embodiment and Example 11 are basically the same, and the difference is: the first metal layer (300) and the second metal layer (600) in step 2) are copper metal layers, and a copper current collector is manufactured. The specific manufacturing steps of the current collector are specifically as follows:

[0140] 1) Manufacturing of fiber base layer (100)

[0141] Nylon 6 and graphene fibers with a mass ratio of 98:2 are mixed, melted, and then extruded to form composite fibers. Then, 50 parts of composite fibers, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica are taken, uniformly mixed, laid out uniformly in a net shape, and hot-rolled and dried to produce a fiber base layer (100) with a thickness of 6 μm.

[0142] 2) Manufacture of the entire house

[0143] A first adhesive layer (200) and a second adhesive layer (500), each having a thickness of 50 nm, are respectively deposited on the upper and lower surfaces of the fiber base layer (100) manufactured in step 1) using vacuum deposition technology, wherein the first adhesive layer (200) and the second adhesive layer (500) are iron metal layers. Then, a first metal layer (300) and a second metal layer (600), each having a thickness of 1000 nm, are continuously deposited on the first adhesive layer (200) and the second adhesive layer (500), wherein the first metal layer (300) and the second metal layer (600) are copper metal layers. Then, a first antioxidant layer (400) and a second antioxidant layer (700) with a thickness of 50 nm are continuously deposited on the first metal layer (300) and the second metal layer (600) (where the first antioxidant layer (400) and the second antioxidant layer (700) are nickel metal layers) to obtain a copper current collector. A related performance test is performed on this, and the test results are as shown in Table 1.

[0144] Example 13

[0145] The method of manufacturing the current collector and the structure of the current collector in this embodiment and Example 11 are fundamentally the same, and the difference is: the material of the inorganic fiber is different. The specific manufacturing steps of the current collector are specifically as follows:

[0146] 1) Manufacturing of fiber base layer (100)

[0147] Nylon 6 and carbon fibers with a mass ratio of 98:2 are mixed, melted, and then extruded to form composite fibers. Then, 50 parts of composite fibers, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica are taken, uniformly mixed, laid out uniformly in a net shape, and hot-rolled and dried to produce a fiber base layer (100) with a thickness of 6 μm.

[0148] 2) Manufacture of the entire house

[0149] A first adhesive layer (200) and a second adhesive layer (500), each having a thickness of 50 nm, are respectively deposited on the upper and lower surfaces of the fiber base layer (100) manufactured in step 1) using vacuum deposition technology, wherein the first adhesive layer (200) and the second adhesive layer (500) are iron metal layers. Then, a first metal layer (300) and a second metal layer (600), each having a thickness of 1000 nm, are continuously deposited on the first adhesive layer (200) and the second adhesive layer (500), wherein the first metal layer (300) and the second metal layer (600) are aluminum metal layers. Then, a first antioxidant layer (400) and a second antioxidant layer (700) with a thickness of 50 nm are continuously deposited on the first metal layer (300) and the second metal layer (600) (where the first antioxidant layer (400) and the second antioxidant layer (700) are nickel metal layers) to obtain an aluminum current collector. A related performance test is performed on this, and the test results are as shown in Table 1.

[0150] Example 14

[0151] The method of manufacturing the current collector and the structure of the current collector in this embodiment and Example 12 are fundamentally the same, and the difference is: the material of the inorganic fiber is different. The specific manufacturing steps of the current collector are specifically as follows:

[0152] 1) Manufacturing of fiber base layer (100)

[0153] Nylon 6 and carbon fibers with a mass ratio of 98:2 are mixed, melted, and then extruded to form composite fibers. Then, 50 parts of composite fibers, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica are taken, uniformly mixed, laid out uniformly in a net shape, and hot-rolled and dried to produce a fiber base layer (100) with a thickness of 6 μm.

[0154] 2) Manufacture of the entire house

[0155] A first adhesive layer (200) and a second adhesive layer (500), each having a thickness of 50 nm, are respectively deposited on the upper and lower surfaces of the fiber base layer (100) manufactured in step 1) using vacuum deposition technology, wherein the first adhesive layer (200) and the second adhesive layer (500) are iron metal layers. Then, a first metal layer (300) and a second metal layer (600), each having a thickness of 1000 nm, are continuously deposited on the first adhesive layer (200) and the second adhesive layer (500), wherein the first metal layer (300) and the second metal layer (600) are copper metal layers. Then, a first antioxidant layer (400) and a second antioxidant layer (700) with a thickness of 50 nm are continuously deposited on the first metal layer (300) and the second metal layer (600) (where the first antioxidant layer (400) and the second antioxidant layer (700) are nickel metal layers) to obtain a copper current collector. A related performance test is performed on this, and the test results are as shown in Table 1.

[0156] Comparative Example 1

[0157] The method of manufacturing the current collector and the structure of the current collector of the Comparative Example and Example 1 are basically the same, and the difference is: the fiber used in the fiber base layer (100) is only Nylon 6. The specific steps are as follows:

[0158] 1) Manufacturing of fiber base layer (100)

[0159] 50 parts of nylon 6, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica are taken and mixed uniformly, then spread uniformly in a net shape, and hot-rolled and dried to produce a fiber base layer (100) with a thickness of 6 μm.

[0160] 2) Manufacture of the entire house

[0161] A first adhesive layer (200) and a second adhesive layer (500), each having a thickness of 50 nm, are respectively deposited on the upper and lower surfaces of the fiber base layer (100) manufactured in step 1) using vacuum deposition technology, wherein the first adhesive layer (200) and the second adhesive layer (500) are nickel metal layers. Then, a first metal layer (300) and a second metal layer (600), each having a thickness of 1000 nm, are continuously deposited on the first adhesive layer (200) and the second adhesive layer (500), wherein the first metal layer (300) and the second metal layer (600) are aluminum metal layers. Then, a first antioxidant layer (400) and a second antioxidant layer (700) with a thickness of 50 nm are continuously deposited on the first metal layer (300) and the second metal layer (600) (where the first antioxidant layer (400) and the second antioxidant layer (700) are nickel metal layers) to obtain an aluminum current collector. A related performance test is performed on this, and the test results are as shown in Table 1.

[0162] Comparative Example 2

[0163] The method of manufacturing the current collector and the structure of the current collector of the present Comparative Example and Comparative Example 1 are basically the same, and the difference is: the first metal layer (300) and the second metal layer (600) of step 2) are copper metal layers. The specific steps are as follows:

[0164] 1) Manufacturing of fiber base layer (100)

[0165] 50 parts of nylon 6, 3 parts of sodium methylcellulose, 3 parts of polyacrylamide, 0.5 parts of glyceryl monostearate, 2 parts of calcium carbonate, 5 parts of polyvinyl alcohol, 2 parts of borax, and 0.2 parts of nanosilica are taken and mixed uniformly, then spread uniformly in a net shape, and hot-rolled and dried to produce a fiber base layer (100) with a thickness of 6 μm.

[0166] 2) Manufacture of the entire house

[0167] A first adhesive layer (200) and a second adhesive layer (500), each having a thickness of 50 nm, are respectively deposited on the upper and lower surfaces of the fiber base layer (100) manufactured in step 1) using vacuum deposition technology, wherein the first adhesive layer (200) and the second adhesive layer (500) are nickel metal layers. Then, a first metal layer (300) and a second metal layer (600), each having a thickness of 1000 nm, are continuously deposited on the first adhesive layer (200) and the second adhesive layer (500), wherein the first metal layer (300) and the second metal layer (600) are copper metal layers. Then, a first antioxidant layer (400) and a second antioxidant layer (700) with a thickness of 50 nm are continuously deposited on the first metal layer (300) and the second metal layer (600) (where the first antioxidant layer (400) and the second antioxidant layer (700) are nickel metal layers) to obtain an aluminum current collector. A related performance test is performed on this, and the test results are as shown in Table 1.

[0168] Comparative Example 3

[0169] The method of manufacturing the current collector and the structure of the current collector in the comparative example and Example 1 are basically the same, and the difference is: the mass ratio of nylon 6 to titanium dioxide nanofibers in the composite fiber is 60:40.

[0170] Comparative Example 4

[0171] The method of manufacturing the current collector and the structure of the current collector in the comparative example and Example 1 are basically the same, and the difference is: the first adhesive layer and the second adhesive layer are not installed.

[0172] Tensile Elongation Test Method: One end of the fiber base layer is mounted to the upper clamp head of the tensile testing machine and the other end to the lower clamp head, maintaining them on the same axis. Parameters such as the machine's specifications, speed, and units are set, and the tensile length and load values ​​of the sample are measured and recorded during the test. Based on the test results, the tensile elongation of the fiber base layer is calculated. When testing tensile elongation, the pressure density is 4 g / cm³. 3 ~4.1g / cm 3 The meaning of pressure density here is the ratio of the tensile force applied to the sample to the cross-sectional area of ​​the sample. Specifically, the test conditions are a temperature between 20°C and 25°C and a relative humidity between 40% and 70%.

[0173] Peel strength test method: Attach a tape 11 cm long to the steel plate, attach a current collector 10 cm long to the tape, attach a tape 22 cm long to the current collector, fix the steel plate to the peel strength tester, bend the tape 22 cm long into a U-shape, grip the free end of the tape with the clip of the peel strength tester, operate the peel strength tester to pull the tape to separate the metal layer and the substrate layer, and test the peel strength. Specifically, the test conditions are: the temperature is between 20°C and 25°C and the relative humidity is between 40% and 70%.

[0174] Electrolyte Infiltration Contact Angle Test Method: The electrolyte is dropped vertically onto the surface of a current collector, and the contact angle between the droplet and the material surface is measured using a contact angle measuring instrument. The temperature is 20°C–25°C and the relative humidity is 40%–70%. The electrolyte is ethylene carbonate.

[0175] Resistivity Test Method: Record the length and cross-sectional area of ​​the current collector sample, place the sample in a test clamp to ensure the clamp makes good contact with the sample surface, and apply a current of a certain magnitude through a resistivity tester. Measure the voltage across the ends of the sample using a voltmeter. Calculate the resistivity of the sample using the resistivity formula based on the measured current and voltage values. Specifically, the test conditions are a temperature between 20°C and 25°C, a relative humidity between 40% and 70%, and a resistance gap of 0.8mm to 1.2mm for the resistivity tester.

[0176] number Tensile elongation (%) Peel strength (N) Electrolyte infiltration contact angle (°) Resistivity (Ω ·m) Example 1 0.32 3.0 75 3.2X10 -8 Example 2 0.35 2.8 73 2.3X10 -8 Example 3 0.21 2.6 70 3.4X10 -8 Example 4 0.23 2.5 68 2.5X10 -8 Example 5 0.41 2.1 78 3.5X10 -8 Example 6 0.43 1.8 77 2.6X10 -8 Example 7 0.35 2.2 76 3.6X10 -8 Example 8 0.35 3.3 73 3.7X10 -8 Example 9 0.42 3.1 76 2.8X10 -8 Example 10 0.32 3.2 72 3.4X10 -8 Example 11 0.33 2.8 74 2.9X10 -8 Example 12 0.37 2.7 71 1.9X10 -8 Example 13 0.28 2.7 74 3X10 -8 Example 14 0.32 2.5 70 2.1X10 -8 Comparative Example 1 0.62 1.1 82 3.8X10 -8 Comparative Example 2 0.66 1.3 80 3X10 -8 Comparative Example 3 0.71 1.4 79 3.7X10 -8 Comparative Example 4 0.33 0.8 72 3.9X10 -8

[0177] The technical features of the embodiments described above may be combined arbitrarily, and for the sake of brevity, not all possible combinations of the technical features of the embodiments have been described; however, as long as there is no contradiction in such combinations of technical features, they should be considered within the scope described in this specification.

[0178] The embodiments described above represent only a few embodiments of the present invention, and while the description is more specific and detailed, it should not be understood as a limitation on the scope of the patent. Persons skilled in the art should note that various modifications and improvements can be made without departing from the spirit of the present invention, and these fall within the scope of protection of the present invention. Accordingly, the scope of protection of the present invention is based on the appended claims.

Claims

Claim 1 A current collector comprising a fiber base layer, wherein a first adhesive layer and a second adhesive layer are respectively installed on both surfaces of the fiber base layer, and a first metal layer and a second metal layer are respectively installed on surfaces of the first adhesive layer and the second adhesive layer that are separated from the fiber base layer, wherein the material composition of the fiber base layer comprises the following compositional parts in weight portions: 50 to 120 parts by weight of composite fiber, 4.1 to 19 parts by weight of inorganic filler, and an auxiliary agent, wherein the composite fiber comprises organic fiber and inorganic fiber, and the inorganic fiber comprises one or more of graphene fiber, carbon fiber, glass fiber, ceramic fiber, metal oxide nanofiber, and silica nanofiber, and the mass ratio of the organic fiber to the inorganic fiber is (70 to 99.9): (0.1 to 30). Claim 2 A current collector according to claim 1, characterized in that the mass ratio of the organic fiber to the inorganic fiber is (90~99.9):(0.1~10). Claim 3 A current collector according to claim 1 or 2, wherein the inorganic filler comprises one or more of calcium carbonate, borax, and nanosilica; and / or the organic fiber comprises one or more of polyethylene terephthalate fiber, polybutylene terephthalate fiber, polyethylene naphthalate fiber, polypropyl carbamate fiber, urethane fiber, polycaprolactone fiber, nylon 6, nylon 66, polyimide fiber, polyacrylonitrile fiber, polyoxyethylene fiber, polyvinyl alcohol fiber, polyvinyl chloride fiber, polyvinylpyrrolidone fiber, cellulose acetate, ethyl cyanoethyl cellulose, polyaniline fiber, and polybenzimidazole fiber. Claim 4 A current collector according to claim 1 or 2, wherein the auxiliary agent comprises one or more of a dispersant, a thickener, an emulsifier, and an adhesive; the dispersant comprises one or more of polyacrylamide, polyvinyl alcohol, sodium citrate, and sodium silicate; the thickener comprises one or more of sodium hydroxypropylmethylcellulose, sodium hydroxyethylmethylcellulose, sodium carboxymethylcellulose, sodium methylcellulose, and sodium algilate; the emulsifier comprises one or more of glyceryl monostearate, polyethylene oxide, and sodium dodecyl sulfate; and the adhesive comprises sodium carboxymethylcellulose and / or polyvinyl alcohol. Claim 5 A current collector according to claim 4, characterized in that the amount of the auxiliary agent added to the fiber base layer is 8.1 to 28 parts by weight, and in the auxiliary agent, the dispersant is 2.5 to 9 parts by weight, the thickener is 3 to 8 parts by weight, the emulsifier is 0.1 to 2 parts by weight, and the adhesive is 2.5 to 9 parts by weight. Claim 6 In claim 1 or 2, the first antioxidant layer and the second antioxidant layer are further included, wherein the first antioxidant layer is located on a surface of the first metal layer separated from the first adhesive layer, and the second antioxidant layer is located on a surface of the second metal layer separated from the second adhesive layer, and the materials of the first antioxidant layer and the second antioxidant layer are each independently Al, Fe, Ni, Zn, Gr, SiO2, Al2O 3, A current collector characterized by being SiC or Si3N4. Claim 7 In claim 1 or 2, the materials of the first adhesive layer and the second adhesive layer are each independently Ni, Zn, Fe, Gr, SiO 2, Al2O 3, A current collector characterized by being Fe2O3 or Si3N4; and / or the material of the first metal layer and the second metal layer being Al or Cu. Claim 8 A current collector according to claim 6, wherein the thickness of the fiber base layer is 2 μm to 8 μm; and / or the thickness of the first adhesive layer and the second adhesive layer is independently 10 nm to 200 nm; and / or the thickness of the first metal layer and the second metal layer is independently 100 nm to 2000 nm; and / or the thickness of the first antioxidant layer and the second antioxidant layer is independently 10 nm to 100 nm. Claim 9 A current collector according to claim 1 or 2, wherein at least one of the first adhesive layer and the second adhesive layer is made of Fe, and the inorganic fiber comprises one or more types selected from graphene fibers and carbon fibers. Claim 10 A current collector according to claim 1 or 2, wherein the inorganic fiber is selected from metal oxide nanofibers, and the materials of the first adhesive layer and the second adhesive layer are each independently selected from metal or metal oxide. Claim 11 A current collector according to claim 1 or 2, wherein the inorganic fiber comprises one or more of graphene fibers, carbon fibers, glass fibers, ceramic fibers, and silica nanofibers, and the materials of the first adhesive layer and the second adhesive layer are each independently selected from non-metallic oxides and non-metallic nitrides. Claim 12 A method for manufacturing a current collector according to claim 1, comprising: a step of manufacturing a fiber base layer by mixing the composite fiber, the inorganic filler, and the auxiliary agent, and then rolling and molding; a step of forming the first adhesive layer and the second adhesive layer on each of the two sides of the fiber base layer, respectively; and a step of forming the first metal layer and the second metal layer on each of the first adhesive layer and the second adhesive layer, respectively, away from the fiber base layer. Claim 13 An electrode sheet characterized by comprising a current collector according to claim 1 and an electrode active material layer located on the surface of the current collector. Claim 14 A battery cell characterized by including an electrode sheet according to claim 13. Claim 15 A battery pack characterized by including a battery cell according to claim 14. Claim 16 An electric device characterized by including a battery cell according to claim 14 or a battery pack according to claim 15. Claim 17 delete

Citation Information

Patent Citations

  • Paper-based composite structure and battery

    CN108281666A